2015
DOI: 10.1242/jeb.110817
|View full text |Cite
|
Sign up to set email alerts
|

Elements of a ‘nervous system’ in sponges

Abstract: Genomic and transcriptomic analyses show that sponges possess a large repertoire of genes associated with neuronal processes in other animals, but what is the evidence these are used in a coordination or sensory context in sponges? The very different phylogenetic hypotheses under discussion today suggest very different scenarios for the evolution of tissues and coordination systems in early animals. The sponge genomic 'toolkit' either reflects a simple, pre-neural system used to protect the sponge filter or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(133 citation statements)
references
References 117 publications
3
127
0
3
Order By: Relevance
“…Therefore, and consistent with the suggestions of Hoffmann et al (2005), H. panicea may perhaps cease its pumping activity to establish internal body anoxia to maintain its endosymbiotic community (Althoff et al 1998, Wichels et al 2006, Schneemann et al 2010. Bacteria isolated from H. panicea are potential sources of neuro-active compounds (Perovic et al 1998), suggesting that sponge-associated microbes also play a functional role in coordinating contractile behavior of the sponge host (Meech 2008, Leys 2015.…”
Section: Relationship Between Osculum Dynamics and Filtration Ratesupporting
confidence: 59%
See 2 more Smart Citations
“…Therefore, and consistent with the suggestions of Hoffmann et al (2005), H. panicea may perhaps cease its pumping activity to establish internal body anoxia to maintain its endosymbiotic community (Althoff et al 1998, Wichels et al 2006, Schneemann et al 2010. Bacteria isolated from H. panicea are potential sources of neuro-active compounds (Perovic et al 1998), suggesting that sponge-associated microbes also play a functional role in coordinating contractile behavior of the sponge host (Meech 2008, Leys 2015.…”
Section: Relationship Between Osculum Dynamics and Filtration Ratesupporting
confidence: 59%
“…Recent studies suggest the osculum senses external stimuli by means of primary cilia that line its inner epithelium (Ludeman et al 2014, Leys 2015. Osculum contractions appear to be stimulated by air exposure (Parker 1910), electrical, mechanical and chemical stimuli (Parker 1910, Prosser et al 1962, Elliott & Leys 2007, and changes in light intensity (Reiswig 1971b) and water flow dynamics .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the basal metazoan groups, definitive neuronal tissue and synapses are found in the cnidarians (jellyfish, corals, sea anemones, hydras) and ctenophores (comb jellies); no definitive neuronal tissue is yet known for placozoans and sponges (Jorgensen 2014; Halanych 2015; Leys 2015). The simplest bilaterians, the flatworms (acoels, planarians, flukes, tapeworms), have definitive brains.…”
Section: Synapse/neuronal Invaginating Projections In the Simplest Anmentioning
confidence: 99%
“…The initial analyses focused on gene content, with emphasis on genes considered to be related to animal multicellularity and complexity, such as those involved in embryonic development, immunity and sensory functions [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. These studies, along with insights from transcriptomes of several other sponge species [63][64][65][66][67], demonstrated that sponges possess representatives of overwhelming majority of animal developmental gene families, including developmental transcription factors [53,54] and components of signalling pathways [6,48-50,55,62].…”
Section: The Genomic Perspectivementioning
confidence: 99%